Cultural methods in psychology : describing and transforming cultures - McLean, Kate C. (Oxford University Press, 2022)
"As I sat down to write this chapter about the use of life story methods for capturing cultural-historical aspects of LGBTQ+ identity development, I was transported back in time... It was a hot summer day in 2004. I had travelled back from the "big city" where I was attending university to visit my family. This was my first summer away from home. At that moment, my family and I sat in the parking lot of a diner, having just finished breakfast at a local greasy spoon-a ritualistic send off before I started my four-hour return drive. In those moments, our car felt unusually cramped. My dad was in the back seat with me, my mom and brother in the front. I didn't have much of an appetite that morning knowing that in mere minutes, I would come out to my family as gay. On our way out of the restaurant, walking to our separate cars, I somehow managed to muster up the courage to tell my family there was something important I wanted them to know. So, there I was, in the backseat of the car with a message for my family. Looking back on it, the message was more like an ultimatum. They could learn to love this new version of me, as I had done, or our routine "see you later" might be a "goodbye." This is the beginning of my story-both my coming out story and, in some ways, my life story. Thankfully, my family is still an important part of this story"